Evaluation of the utility efficiency of subway stations based on spatial information from public social media. (September 2018) - Liu, Xin; Macedo, Joseli; Zhou, Tao; Shen, Liyin; Liao, Yilan; Zhou, Yulin
Abstract: Subway systems are important for urban transport, and effective subway systems should meet the travel needs of urban transport users. A critical feature of a subway system is the location choice of subway stations. These locations should maximize the utility value of subway stations for residents, thus contributing to ease of accessibility and level of mobility. Traditionally, the utility evaluation of subway systems has been based on static and unilateral information. This study describes the utility efficiency of subway stations in Central Chongqing, China, by assessing the balance between the supplied train services and the travel needs of the population. The information used in this study was taken from public social media; therefore, the decision-making process was bilateral, with the public voting for a subway station with "their feet". Spatial analysis, including methods of hot spot analysis, buffer zone analysis and spatial stratified heterogeneity analysis, were used to test this process. The results indicated that spatial inequality of utility efficiency of subway stations still exists; however, the extent of the spatial inequality was dependent on the size of the walking catchment area and their location, be it within the city center or in more remote areas.